Efforts To Increase The Efficiency Of Wireless Power Transfer (Literature Study) - Jawahir, Jawahir (Journal Sensi: Strategic of Education in Information System, 2025)
One of the important issues in the electric power system is the problem of distributing electrical energy from one place to another which is relatively expensive. In addition to requiring many cables/conductors and a good protection system, the installation is also not easy. Therefore, the cost of installing the distribution channel will be expensive. In addition, the stretch of cables/conductors can interfere with the beauty of the room. For this reason, experts have conducted research for quite a long time to design an electrical energy distribution system that can be used to distribute electrical energy without using cables or wirelessly. With this wireless system, in addition to saving cable material costs and maintenance costs, it can also reduce heavy loads. In addition, the stretch of cables/conductors does not interfere with the beauty of the room. Wireless Power Transfer System (WPT) is a system for distributing electrical energy from one place to another without using cables. In other words, the system for distributing electrical energy from one device to another without passing through physical media in the form of electrical cable/conductor channels. With the development of WPT technology, the electrical energy distribution system that occurs can be more efficient and easier to install. Many studies have been conducted by experts to improve the efficiency of the power distributed. Efforts that have been made are for example by adding a barrier (shielding), adding metamaterials, making coil designs in circular and hexagonal shapes, using antennas made of aluminum or copper, and so on. With the results of this study, it is hoped that one day this wireless electrical energy distribution technology can be implemented with high efficiency.